Feasibility and Efficacy of BLE Beacon IoT Devices in Inventory Management at the Shop Floor - Ravi Ramakrishnan; Loveleen Gaur; Gurinder Singh (Institute of Advanced Engineering and Science, 2016)
Inventory Management is a key area for customer service and cost optimization in any manufacturing setup. As companies turn global and have thousands of components and hundreds of warehouses the inventory becomes a nightmare and a lot of time is spend in tracking inventory and ensuring right shipments. Traditional systems of robotic arms for inventory pick and drop have been based on premises of marking areas of the warehouse and tracking it. However with the advent of IoT all this is set to change as inventory objects become more self-aware and self-broadcasting. This paper technically suggests an approach of managing inventory using low energy blue tooth beacons and also does a statistical case research on two groups of the same organization one before the pilot run where traditional barcode scanners are used to track inventory and other one where the pilot trial BLE beacon technology was used. Statistically the IoT-beacon users are much more efficient and accurate and save lot of time and costs in the short run itself.